The prospectus disclosure regulatory regime in Malaysia / Mohammad Rizal Salim - Salim, Mohammad Rizal (Faculty of Administratron and Law, 2001)
The relationship between the issuer and subscribers of securities has traditionally been based on the law of contract whereby misrepresentation, whether innocent or fraudulent, will result in the contract being rendered voidable. In addition, the law imposes an obligation on the issuer of securities to disclose certain specified1 and relevant2 information. One may wonder why there is a need to disclose information for the issue of securities. Consider if the legislature enacts a law requiring car salesmen to disclose all information relating to the car to potential purchasers. Or any other merchandise, for that matter. What is the difference between cars and securities?